Innovative Leadership of Kiai in the Management of Integrated Curriculum in Pesantren - Deden Ramdhani; Imron Arifin; Akhmad Fauzi Hamzah (UII Darullughah Waddawah Pasuruan, 2026)
This study examines the innovative leadership of K.H. Chasan Zamzami in integrated curriculum management at API Al Hanafiyah Islamic Boarding School, Jatiwangi, Majalengka. The issue addressed is the gap between traditional pesantren education and modern formal curriculum demands. The purpose of this research is to analyze how kiai leadership innovation integrates salaf and formal curricula. The method used is a descriptive qualitative approach with a case study design, collecting data through in-depth interviews, participant observation, and documentation study. The results reveal that K.H. Chasan Zamzami's innovative leadership is manifested through five integrated dimensions: spiritual development, student development through structured character education, social innovation through community organizations, special guidance for adolescents, and cadre formation through integrated curriculum and dual-certificate system. The impact of this research contributes to the development of Islamic education management theory by offering an integrated innovative leadership model. The conclusion confirms that this leadership model combines Islamic spiritual values, modern educational management, and community empowerment, which can be replicated by other Islamic boarding schools. Keywords: Curriculum Integration; Innovative Leadership; Islamic Boarding School; Kiai; Pesantren